Women and Children as Victims and Offenders: Background, Prevention, Reintegration: Suggestions for Succeeding Generations (Volume 2) - Kury, Helmut; Redo, Sławomir; Shea, Evelyne (SpringerLink Bücher, 2016)
Volume 2 Part IV: The role of crime prevention: Punishment – imprisonment - alternative sanctions -- Part V: Crime Prevention: Proactive Strategies -- Part VI: Final Discussion .